Innovation of Kepok Banana Hump Bread (Musa paradiciasa L.) as Diabetes Diet Therapy: Literature Review - Nur, Liesna Lusyana; Rakhman, Fani Khairunnisa; Arafani, Nabilah; Wibowo, Nura'isyah Indah (Universitas Muhammadiyah Surakarta, 2021)
Purpose: Diabetes has become a health problem that causes chronic complications such as heart disease, kidney failure and the risk of death which can reduce life expectancy and can increase mortality rates therefore intervention is required, especially in dietary intake. Management of low-carbohydrate and high-fiber diet is important for diabetics to prevent the occurrence of other complications. Kepok Banana Hump Bread could be alternative food choice for diabetes mellitus diet. This paper to review the Kepok Banana Hump Bread innovation as diet therapy for diabetics. Methodology: This research using a literature review method pra experimental, true experimental, and literature review of research designs from 20 international and national journals. The literature search was carried out on the Google Scholar and Researchgate databases using three keywords, namely analysis of antidiabetic compounds on the Kepok Banana Hump; the potency of the Kepok Banana Hump; the impact of Kepok Banana hump powder on blood sugar levels. Results: Kepok Banana Hump Bread that utilizes Kepok Banana Hump Flour in its production can be an alternative in diet management. Kepok Banana Hump Flour contains 25.5 glycemic index and 26,72% fiber. The addition of 40% banana hump flour can produce a distinctive flavor of banana hump flour with a strong taste, rough texture, slightly hard, and dark brown color. This Kepok Banana Hump Bread innovation is expected to be an alternative diet in the process of treating diabetes mellitus.